2001
DOI: 10.1097/00001756-200101220-00029
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-2 and interleukin-4 increase the survival of retinal ganglion cells in culture

Abstract: Natural cell death is a degenerative phenomenon observed during the normal development of the nervous system. The neuroprotective effects of cytokines produced by neuronal, glial or infiltrating cells on neurons have been extensively studied. In this work we studied the role of interleukin (IL)-2 and IL-4 on the survival of retinal ganglion cells (RGC) after 48 h in culture. Our results demonstrate that the effect of both ILs was dose-dependent and the treatment with either IL-2 (50 U/ml) or IL-4 (5 U/ml) indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…Several studies have demonstrated multiple effects of cytokines upon the visual system [25,28,29]. Here, we investigated whether in vivo IL-6 treatment modulates the distribution of retinotectal axons during the development of visual circuits.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated multiple effects of cytokines upon the visual system [25,28,29]. Here, we investigated whether in vivo IL-6 treatment modulates the distribution of retinotectal axons during the development of visual circuits.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the endogenous mechanisms that minimize the pathological effects of increased mechanical strain on the neurons is a key target in preventing their loss in disease. Although aberrant immune signaling has been implicated in the pathogenesis of glaucoma (Tezel and Wax, 2004; Grus et al, 2008; Wax and Tezel, 2009; Križaj et al, 2014), certain cytokines have also been recognized for their ability to protect ganglion cells (Sholl-Franco et al, 2001; Sappington et al, 2006). It is tempting to propose that the increased expression of mRNA for IL-3 and IL-3Rα in eyes exposed to moderate IOP elevation may be part of an endogenous protective response, although this requires further confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively low concentration of the muscarinic receptor agonist carbamycholine was found to significantly increase the survival of retinal neurons via M1 muscarinic receptors (Pereira et al 2001). Also, IL-4 increased the survival of retinal neurons mediated by the activation of M1 muscarinic receptors (Sholl-Franco et al 2001). Directly depending on M1 muscarinic receptor activation, cAMP played an important role in controlling the survival of retinal neurons (Santos and Araujo 2001).…”
Section: Introductionmentioning
confidence: 94%